1996
DOI: 10.1021/ja961988t
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of the Nonspecific Hydroxyl Radical Generator,N-Hydroxypyridine-2(1H)-thione

Abstract: The photochemistry of N-hydroxypyridine-2(1H)-thione (N-HPT) has been investigated in aqueous and organic solvents using laser flash photolysis (λ exc ) 308 or 355 nm). Independent of the environment, UV excitation of N-HPT causes homolytic N-O bond cleavage, which leads to formation of the 2-pyridylthiyl (PyS • ) and hydroxyl ( • OH) radicals. In aqueous media, this process occurs efficiently from both the anionic and neutral forms (Φ N-O ≈ 0.20-0.30). In addition to N-O bond scission, N-HPT undergoes other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 43 publications
9
85
1
Order By: Relevance
“…Redmond and co-workers used this reaction for the detection of • OH radicals that are formed as a result of the laser flash photolysis of N -hydroxy-2(1 H )-pyridone and N -hydroxypyridine-2(1 H )-thione 59. In the photolysis of AAPH, the formation of • OH radicals can be excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Redmond and co-workers used this reaction for the detection of • OH radicals that are formed as a result of the laser flash photolysis of N -hydroxy-2(1 H )-pyridone and N -hydroxypyridine-2(1 H )-thione 59. In the photolysis of AAPH, the formation of • OH radicals can be excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Redmond and co-workers have reported that laser photolysis of aqueous solutions of N-HPT at 355 nm produced hydroxyl radicals with quantum yields of 12-24% as determined by reaction of the hydroxyl radical with thiocyanate (23). We investigated the steady-state photolysis of dilute (1 mM) solutions of N-HPT and found that 5 min of irradiation with a lamp at 350 nm was sufficient to convert most of the N-HPT to products.…”
Section: Discussionmentioning
confidence: 99%
“…N-HPT generates several reactive intermediates upon photolysis in neutral aqueous solutions where N-HPT is largely ionized (Scheme 1; 23). They include the 2-pyridylthiyl radicals, the N-oxy-2-pyridylthiyl radicals, and a solvated electron (the latter two occurring as a result of photoionization with Φ e-) 0.05 at 355 nm) in addition to hydroxyl radicals (23). It is possible that the pyridylthiyl radicals may initiate RNA cleavage during our reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some photochemical sources of oxyl radicals, which display DNA oxidizing activity (strand breaks and base modification under relatively mild conditions), have been reported during the last decade (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). N-hydroxy-and N-alkoxypyridinethiones 1 (Chart 1) have served as convenient oxyl radical sources to assess oxidative damage (6,7); indeed, the molecular mechanism of their photooxidative DNA damage has been studied thoroughly (14)(15)(16)(17). Although pyridinethiones 1 are readily available and serve as efficient oxyl-radical sources, their DNA damage is complicated: not only do the photoreleased oxyl radicals cause strand breaks and base modifications, but the photoproducts of the pyridinethiones display significant photosensitizing DNA damage (14).…”
Section: Introductionmentioning
confidence: 99%